A Call for Interfacing Measures of Instrumental Activities of Daily Living Across the Transition of Care. (January 2019) - Koyfman, Irina; Finnell, Deborah
Abstract : The ability to maintain functional status is an essential aspect of self-care for older adults. Instrumental activities of daily living (IADLs) decline within hours of hospitalization and are often overlooked, underassessed, and underreported. The aim of this integrative review was to examine and compare methods used to assess IADLs to determine the best measure for use across the care continuum, especially during transitions of care. A literature search without date restrictions was conducted using PubMed, Cumulative Index of Nursing and Allied Health Literature (CINAHL), and Embase databases. Twelve studies of moderate quality were included in this review. More than half (58%) of the studies utilized the Lawton and Brody Scale to measure IADL among home-based and hospitalized patients. Implementation of this scale as standard practice and sharing the results with healthcare providers would encourage continuity of care with the goal of supporting older adults aging in place and preventing rehospitalization. In turn, this communication process may improve the transition from the inpatient to home setting, where, since 1999, the Outcome and Assessment Information Set has been mandated.